Theoretical study on wavelength conversion using cross-polarization modulation in a single semiconductor optical amplifier - Wang, Fei; Xia, Guangqiong; Wu, Zhengmao (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Wavelength conversion based on the cross-polarization modulation (XPM) in a single semiconductor optical amplifier (SOA) has been numerically investigated by using the theoretical model in which the birefringence has been taken into account. The results show that the non-inverted and inverted wavelength conversion can be realized through selecting reasonably the parameters; there exit some differences in the chirp, extinction ratio (ER), and eye diagram of the converted signal between the non-inverted and inverted conversion; with the increase of the bit rate, the chirp increases and the eye opening ratio (EOR) decreases.
Optica Applicata, Vol. 35, 2005, nr 2, s. 365-375
Keywords: optyka; wavelength conversion; cross-polarization modulation; semiconductor optical amplifier